Bullying in Egyptian school children in relation to malocclusion and poor dental esthetics - Sweidan, Ayman Tarek Hassan (2022)
Many people especially children get bullied these days and suffer from its consequences. Bullying is intended physical, social, and/or psychological harm by continuous misuse of power in relationships through verbal, physical, and/or social behavior. Bullying has been observed for a long time, and its prevalence is increasing all over the world and turning into a global concern and it is related to low self-esteem and other long-term consequences. The prevalence of bullying in different countries differs according to time, region, gender, age, socio-economic level, and the instrument used to measure the prevalence. Many factors increase the risk of being bullied and are linked to this behavior like self-perceived socioeconomic disadvantage and compromised physical appearance which is reported to be the most frequent reason for bullying. Deviations in dental appearance and malocclusion could be an important target for teasing among students as it compromises the physical and facial appearance as well as influences the perception of a person's friendliness, socioeconomic status, popularity, and IQ. Malocclusion has a psychological impact as well as functional disorders as it affects the OHRQoL and could lead to low self-esteem. Consequently, a link between malocclusion and the risk of being bullied, the child$1 (Bs self-esteem, and their OHRQoL is most likely possible. The aim of the study was to examine the prevalence of bullying in Egyptian schools of different socio-economic levels and the relationship between bullying, malocclusion, self-esteem, and oral health-related quality of life (OHRQoL). This information will benefit the Egyptian community at large and will help settle the debate about whether or not early orthodontic treatment is necessary. The sample consisted of a sample of three hundred and twenty-four school children of both genders aged 11 to 14 years from different school types of different socio-economic levels (108 school children from each school type) within the New Cairo district during the school year 2019/2020. The participants were asked to fill out 3 questionnaires addressing bullying, self-esteem, and OHRQoL. Olweus bully/victim questionnaire was used to test for bullying and two questions were added to the original questionnaire to customize it to the orthodontic field, the first is one questioning whether the participant is undergoing orthodontic treatment and the other targeting bullying due to orthodontic treatment if the participant was undergoing orthodontic treatment. The Harter$1 (Bs Self Perception Profile for Children was used to assess the participants$1 (Bself-esteem and CPQ11-14 was used to measure the OHRQoL. Clinical assessment was made on the participants to measure the orthodontic treatment need according to the IOTN with its two components DHC and AC and the class of occlusion according to Angle$1 (Bs classification of occlusion. The prevalence of bullying in the different socio-economic level schools was then checked as well as the self-esteem, OHRQoL, IOTN score, and occlusion status of the bullied and non-bullied participants. The results showed that the overall prevalence of bullying was 61.7%. Governmental schools showed the highest prevalence of bullying (76.9%) followed by international schools (54.6%) and then Private schools (53.7%). Regarding the IOTN DHC, related to the total number of participants diagnosed in each grade, grade 4 had the highest prevalence of bullying (78%) while grade 1 had the least bullying prevalence (38%).s
supervisors, Dr. Nagwa Helmy El-Mangoury, Professor of Orthodontics, Faculty of Oral and Dental Medicine, Future University, Dr. Amr Ragab El-Beialy, Associate Professor of Orthodontics, Faculty of Dentistry, Cairo University, Dr. Heba Mohamed Dehis, Lecturer of Orthodontics, Faculty of Dentistry, Cairo University.
Thesis (M.Sc.)-Future University in Egypt, Faculty of Oral and Dental Medicine, Department of Orthodontics, 2022.
Includes bibliographical references.
Text in English, abstracts in English and Arabic.
Keywords: Bullying in schools -- Egypt; Orthodontics, Corrective Methods; Malocclusion -- Treatment